Hubungan Karakteristik dengan Status Gizi Lanjut Usia di Pekon Parerejo Kecamatan Gadingrejo Kabupaten Pringsewu - Annisa Septy Erviani, Annisa Septy Erviani; Abdullah, Abdullah; Khairani, Masayu Dian; Muharramah, Alifiyanti (Journal Aisyah University, 2025)
ABSTRACT The problem of malnutrition in the elderly is easily seen through general appearance. The purpose of this study was to determine the relationship between characteristics and nutritional status of the elderly in Pekon Parerejo, Gadingrejo District, Pringsewu Regency. This research method uses analytic quantitative research using a cross-sectional approach. The population in this study were 65 elderly people with a sample size of 50 respondents selected by purposive sampling. Data analysis using chi square test and gamma test. The results showed that nutritional status was thin 24 (48.0%) respondents, very thin 7 (14.0%) respondents and obese 4 (8.0%) respondents. Female gender was 33 (66.6%) respondents and male 17 (34.0%) respondents. The age of respondents was 45-55 years (52.0%) and 56-59 years (48.0%), while the education level of respondents was elementary school (84.6%), junior high school (10.0%) and high school (6%). The results of statistical analysis showed there was no relationship between gender and nutritional status, p-value = 0.065 (p-value >α = 0.05), there was a relationship between age and nutritional status, p-value = 0.030 (p-value <α = 0.05), and there was no relationship between education level and nutritional status, p-value = 0.151 (p-value >α = 0.05). The conclusion drawn is that nutritional status is related to age so it is recommended that people pay attention to their nutritional status by periodically measuring height and weight. Keywords: Characteristics, Elderly, Nutritional Status, Reference : 25 (2012-2024) ABSTRAK Masalah kurang gizi pada lansia terlihat dengan mudah melalui penampilan umum,. Tujuan penelitian ini untuk mengetahui hubungan karakteristik dengan status gizi lanjut usia (lansia) di Pekon Parerejo Kecamatan Gadingrejo Kabupaten Pringsewu. Metode Penelitian ini menggunakan penelitian kuantitatif analitik dengan menggunakan pendekatan Cross- Sectional. Populasi dalam penelitian ini adalah lansia sebanyak 65 lansia dengan jumlah sampel sebanyak 50 responden yang dipilih secara purposive sampling. Analisis data menggunakan uji chi square dan uji gamma. Hasil penelitian diketahui status gizi kurus 24 (48,0%) responden, sangat kurus 7 (14,0%) responden dan obesitas 4 (8,0%) responden. Jenis kelamin perempuan sebanyak 33 (66,6%) responden dan laki-laki 17 (34,0%) responden. Umur responden 45-55 tahun (52,0%) responden dan umur 56-59 tahun (48,0%) responden, sedangkan tingkat pendidikan responden yaitu SD (84,6%) responden, SMP (10,0%) responden dan SMA (6%) responden. Hasil analisis statistik menunjukkan tidak ada hubungan jenis kelamin dengan status gizi, nilai p value = 0,065 (p-value >α = 0,05), ada hubungan umur dengan status gizi, nilai p-value = 0,030 (p-value <α = 0,05), dan tidak ada hubungan tingkat pendidikan dengan status gizi, nilai p-value = 0,151 (p-value >α = 0,05). Kesimpulan yang diambil yaitu status gizi berhubungan dengan umur sehingga disarankan agar supaya memperhatikan status gizinya secara berkala mengukur tinggi badan dan berat badan Kata Kunci : Kata Kunci : Karakteristik, Lanjut Usia, Status Gizi,